Beating the hackers. - Hancock, Matt (Prospect, 2017)
The article discusses the need of preventing hacking in Great Britain by improving cybersecurity. It states the impact of digital technology on the society, and mentions concerns over use of smart cars like breach of personal data and traffic safety. It notes role of the National Cyber Security Centre (NCSC) in ameliorating internet security, and cites that government has a special responsibility to protect the essential services.